CHRONIC KIDNEY DISEASE AMONGST SICKLE CELL ANAEMIA PATIENT AT THE UNIVERSITY OF MAIDUGURI TEACHING HOSPITAL, NORTH EASTERN NIGERIA: A STUDY OF PREVALENCE AND RISK FACTORS - Audu Abdullahi Bukar; Mohammad Maina Sulaiman; Adama Isa Ladu; Aisha Mohammed Abba; Mohammed Kabir Ahmed; Gideon Thomas Marama; Usman Ali Medugu Abjah (Mediterranean Journal of Hematology and Infectious Diseases)
ABSTRACT